2001
DOI: 10.1159/000049280
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Depression, Anxiety and Quality of Life: A Study of Stroke Patients Compared to Chronic Low Back Pain and Myocardial Ischemia Patients

Abstract: The prevalence of anxiety disorders and depression is assessed as between 20 and 50% following stroke. Depressive persons tend to give their overall life situation a worse rating than their relatives or physicians because of negative cognitions. Nevertheless, research concerning Quality of Life (QoL) after stroke hardly ever takes into account the methodological bias of assessing QoL only by self-rating. The aim of this study was to point out the important relationship between depression, anxiety and the autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 26 publications
2
37
1
2
Order By: Relevance
“…On the one hand, this is particularly astonishing, as dramatic negative consequences of depressive disorders after stroke were found in many studies: depressed mood after stroke was associated with a poorer outcome of rehabilitation therapy [16,24,28,34], with cognitive impairment [15,16], with a markedly reduced quality of life of patients [5,12,18,33] and their caregivers [19], and not at least with an increased risk of subsequent mortality in a 10-year followup [25]. On the other hand, the lack of therapeutic evidence is partly due to difficulties to diagnose validly both depression and antidepressant treatment effects after stroke: a considerable number of patients suffers from cognitive impairment and/or aphasia, which make a valid diagnosis impossible.…”
mentioning
confidence: 99%
“…On the one hand, this is particularly astonishing, as dramatic negative consequences of depressive disorders after stroke were found in many studies: depressed mood after stroke was associated with a poorer outcome of rehabilitation therapy [16,24,28,34], with cognitive impairment [15,16], with a markedly reduced quality of life of patients [5,12,18,33] and their caregivers [19], and not at least with an increased risk of subsequent mortality in a 10-year followup [25]. On the other hand, the lack of therapeutic evidence is partly due to difficulties to diagnose validly both depression and antidepressant treatment effects after stroke: a considerable number of patients suffers from cognitive impairment and/or aphasia, which make a valid diagnosis impossible.…”
mentioning
confidence: 99%
“…Sin embargo, a pesar de esto un gran porcentaje no recibe diagnóstico ni tratamiento adecuados, por lo que nuestro objetivo principal es presentar una herramienta que facilite la identificación de individuos en riesgo a fin de brindarles la atención requerida. 38 Existen diferentes puntos de interés referente a los resultados obtenidos en este estudio. Si observamos la caracterización de la población podemos observar que presenta similitudes con las características de la población en general; en lo referente a los diagnósticos neurológicos llama la atención la prevalencia de pacientes con epilepsia (37.3% de pacientes sin epilepsia vs. 62.7% de pacientes con este diagnóstico).…”
Section: Discussionunclassified
“…On the other hand, the elevated plus-maze test revealed that saline-treated 2VO rats showed significant decrease in time spent on the open arms, as compared with control rats, reflecting anxiogenic effects of ischemic/reperfusion. Indeed, clinical studies have shown that the prevalence of depressive illness and anxiety disorders is 20% -50% following a stroke (27). The hippocampus is a pivotal region for emotional expression, along with limbic and prelimbic areas, including the amygdala and frontal cortex (28,29).…”
Section: Discussionmentioning
confidence: 99%